$δ$-fuzzy Ideals in MS-algebras - Berhanu Assaye Alaba; Mihret Alamneh Taye; Teferi Getachew Alemayehu (International Journal of Mathematics And its Applications, 2018)
In this paper, we introduce the concept of $ δ $-fuzzy ideals and $ α $-level principal $δ $-fuzzy ideals in an MS-algebra and study basic properties of these ideals with respect to homomorphisms. It is observed that the class of all $ δ $-fuzzy ideals forms a complete distributive lattice and the class of all $ α $-level principal $ δ $-fuzzy ideals forms a de Morgan algebra. A characterization of $ δ $-fuzzy ideals in terms of $ α $-level principal $ δ $-fuzzy ideals is given.